Lee Krasner a biography - Levin, Gail 1948- (HarperLuxe, 2011)
"Lee Krasner, best known as Jackson Pollock's wife, reveals a woman who was a firebrand and trailblazer for women's rights, who also led a fascinating life, and who is finally now being recognized as one of the 20th century's modernist masters"--